2012
DOI: 10.1590/s1517-83822012000300025
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Genetic characterization of Porcine circovirus 2 (PCV2) in Brazilian wildlife boars

Abstract: A semi-intensive wildlife boars farm presented a clinical history of high mortality in 70 -90 days-old pigs (> 50 %). Two 90 days-old animals with weight loss and wasting were necropsied and the samples tested for PCV2 by polymerase chain reaction (PCR). The genetic material of PCV2 was sequenced and classified into the PCV2a genotype together with PCV2 sequences obtained from samples of Poland, Brazil, Slovenia and Greece wild boars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…In fact, despite PCV2 being identi ed as a swine pathogen in the late 90s, retrospective studies and analysis based on the molecular clock revealed a much more ancient origin and undetected circulation [6]. Similarly, di erent studies have revealed PCV2 infection in wild boars and other wild animals, although negligible evidence of clinical signs has been provided in these species [7][8][9][10][11][12][13]. Also, extensively raised pigs appeared less a ected.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, despite PCV2 being identi ed as a swine pathogen in the late 90s, retrospective studies and analysis based on the molecular clock revealed a much more ancient origin and undetected circulation [6]. Similarly, di erent studies have revealed PCV2 infection in wild boars and other wild animals, although negligible evidence of clinical signs has been provided in these species [7][8][9][10][11][12][13]. Also, extensively raised pigs appeared less a ected.…”
Section: Introductionmentioning
confidence: 99%
“…PDCoV was first discovered in Hong Kong, China, in 2012 in a territory-wide molecular epidemiology study in mammals and birds (Woo et al, 2012). PDCoV was subsequently reported in the United States in 2014 (Castro et al, 2012;Wang et al, 2014) and then in South Korea, mainland China, Japan, Thailand, Viet Nam and Lao People's Democratic Republic (Lao PDR) (Lee and Lee, 2014;Lorsirigool et al, 2016;Saeng-Chuto et al, 2017a;Song et al, 2015). The coinfection of PDCoV with other enteric viral pathogens such as PEDV, rotavirus or kobuvirus are commonly reported (Mai et al, 2018;Marthaler et al, 2014a;Marthaler et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…The detection of the PCV2 ORF1 and ORF2 genes, and PCV3 ORF1 gene were previously reported (Castro et al 2012;. The PCV2 strain Stoon 1010 obtained from The Scientific Veterinary Institute "Novi Sad" from Novi Sad, Serbia, and an internal reference PCV3 strain from the Department of Microbiology of the Faculty of Veterinary Medicine, University of Belgrade served as the controls.…”
Section: Pcv2 and Pcv3 Detectionmentioning
confidence: 91%